Tenofovir alafenamide in the treatment of chronic hepatitis B: design, development, and place in therapy - Ogawa E; Furusyo N; Nguyen MH (Dove Medical Press, 2017)
Eiichi Ogawa,1 Norihiro Furusyo,1 Mindie H Nguyen2 1Department of General Internal Medicine, Kyushu University Hospital, Fukuoka, Japan; 2Division of Gastroenterology and Hepatology, Department of Medicine, Stanford University Medical Center, Palo Alto, CA, USA Abstract: Tenofovir alafenamide (TAF), a novel prodrug of tenofovir (TFV), has been approved for the treatment of chronic hepatitis B virus (HBV) infection. TAF has been shown to be a potent inhibitor of HBV replication at a low dose, with high intracellular concentration and more than 90% lower systemic TFV concentration than tenofovir disoproxil fumarate (TDF). In two randomized, double-blind, multinational, Phase 3, non-inferiority trials for hepatitis B e antigen (HBeAg)-positive and -negative patients (primary analysis: 48 weeks), TAF 25 mg orally once-daily was not inferior to TDF 300 mg in achieving an HBV DNA level <29 IU/mL at week 48. No amino-acid substitutions associated with viral breakthrough were detected by deep sequencing, and no resistance to TAF was found through week 96. In addition, no difference in the frequency of HBeAg or hepatitis B surface antigen loss was observed. However, TAF was associated with a significantly higher ALT normalization rate than was TDF, based on the American Association for the Study of Liver Diseases criteria (male: ALT ≤30 U/L and female: ALT ≤19 U/L). An analysis of renal safety showed that patients treated with TAF had a significantly lower decrease in the estimated glomerular filtration rate level than did patients treated with TDF. Similarly, the declines of hip and spine bone mineral density were significantly less in the TAF group. These trends of efficacy and renal/bone safety continued through week 96. Longer term follow-up and real-world data will be required to determine if the differences in viral/biochemical response and renal/bone safety seen with TAF in comparison with TDF are clinically relevant. Keywords: hepatitis B virus, treatment, tenofovir alafenamide, tenofovir disoproxil fumarate, adverse effects